Efficacy and safety of antioxidants and dietary therapies for epilepsy: an umbrella meta-analysis - Feng, Yingqi; Cai, Shanshan; Wang, Mengyao; Guo, Yujia; Zhou, Ziyu; Wang, Rutong; Yang, Shen (Frontiers in Nutrition, 2026)
BackgroundEpilepsy is a prevalent chronic neurological disorder. A substantial proportion of patients develop drug-resistant epilepsy. Existing antiepileptic drugs are associated with adverse effects and demonstrate limited efficacy in refractory cases. Oxidative stress plays a critical role in the pathogenesis of epilepsy. Antioxidants such as vitamin D, vitamin E, and melatonin, as well as dietary therapies like the ketogenic diet, have garnered attention as potential adjunctive treatments. However, existing studies exhibit significant controversy and heterogeneity.ObjectiveTo evaluate the efficacy and safety of antioxidants and dietary therapies in the treatment of epilepsy, and to provide evidence-based support for clinical decision-making.MethodsSystematic searches were conducted in PubMed, Web of Science, Embase, and the Cochrane Library. Eighteen eligible meta-analyses were selected for umbrella review based on predefined criteria. Pooled relative risks (RR) with 95% confidence intervals (CI) were calculated using random-effects or fixed-effects models. Heterogeneity was assessed using the I2 statistic, and evidence quality was evaluated with the AMSTAR 2 tool.ResultsDietary therapies—particularly the Low Glycemic Index Treatment (LGIT)—significantly increased the likelihood of achieving ≥50% (RR: 1.95; 95% CI: 1.58–2.33) and ≥90% (RR: 3.33; 95% CI: 1.51–5.14) seizure reduction. However, dietary therapies were ineffective in achieving seizure freedom (RR: 0.68; 95% CI: 0.00–1.36). In subgroup analyses of ≥50% seizure reduction, antioxidants did not demonstrate significant efficacy. Both antioxidants and dietary therapies significantly increased the overall incidence of adverse events (RR: 1.56; 95% CI: 1.19–1.92). Specifically, the ketogenic diet elevated the risks of dyslipidemia (RR: 3.56; 95% CI: 2.00–5.11), weight loss (RR: 4.80; 95% CI: 3.43–6.17), constipation (RR: 3.02; 95% CI: 1.55–4.48), and kidney stones (RR: 5.24; 95% CI: 3.73–6.74). Melatonin was ineffective in reducing seizure frequency (RR: 0.30; 95% CI: 0.00–0.63). Considerable heterogeneity was observed across studies.ConclusionDietary therapies—notably LGIT—demonstrate clear efficacy in reducing seizure frequency but do not facilitate seizure freedom. Current evidence does not support the use of antioxidants as effective adjunctive therapy for epilepsy. These interventions, particularly the ketogenic diet, are associated with increased risks of adverse effects, necessitating careful benefit–risk assessment in clinical application.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251166437, identifier: CRD420251166437.